Altered expression of Bcl-2 and Bax in follicles within dehydroepiandrosterone-induced polycystic ovaries in rats - Bas, Diana Ester (2011)
PCOS (polycystic ovary syndrome) is a heterogeneous disease characterized by hyperandrogenaemia, hirsutism, oligo- or amenorrhea, insulin resistance and anovulation. The aim of the present study was to evaluate if the balance between the ovarian expression of Bax (proapoptotic protein) and Bcl-2 (antiapoptotic protein) is altered in a PCOS model developed in rats by DHEA (dehydroepiandrosterone) administration. In addition, the ovarian morphology and the circulating progesterone levels were evaluated. Histological studies confirmed the presence of follicular cysts, atretic follicles and the absence of corpora lutea in the ovaries from the PCOS group and a significant decrease in circulating progesterone levels. Immunohistochemical studies showed that the expression of Bcl-2 and Bax were mainly localized in granulosa cells of AFs (antral follicles) in both groups. Bax expression was greater in preantral and AFs from PCOS ovarian sections than in the controls. In contrast, intense Bcl-2 immunostaining was observed in the control AFs, while Bcl-2 protein was either absent in PFs (preantral follicles) or weakly expressed in AFs from PCOS rats. These results were partially confirmed by western studies. Data revealed that the ovarian level of Bcl-2 protein was lower in PCOS than in the control and that there were no differences in Bax ovarian levels between groups. However, Bax/Bcl-2 ratio was significantly higher in PCOS group than in the control group. In conclusion, an increase in ovarian apoptosis through an imbalance among the Bcl-2 family members may be involved in the transformation of growing follicles in cystic follicles in the ovaries from DHEA-induced PCOS rats.